Using ion-selective electrodes in environmental monitoring - Tychkov, Vladimir; Trembovetskaya, Ruslana; Kisil, Tatyana; Bondarenko, Yulia (International Conference “Environmental Engineering”, 2017)
Environmental monitoring is an integral part of environmental protection. Control of hazardous substances wastewater occurs both in the laboratory and on-site sampling. The paper provides a method of injection analysis, which is used in data-measuring systems control the parameters of chemical and technological processes using flow-injection method. The method involves sequential injection analysis of the liquid sample supply for the hydraulic lines in the flow measuring channel slot detector. The detector is equipped with two solid-state heterogeneous ion elective electrodes. Before measuring the detector further comprising sample preparation and filtration of samples. The estimation of the uncertainty of the measuring system with the use of ion elective electrodes one of which performs the function of the measuring electrode, while the second an auxiliary. The ultrasonic sample preparation technique, which reduces the impact of uncertainty on the stage of sampling and preparation of samples for analysis is designed. The use of ultrasonic sample preparation directly into the stream allowed expanding the use of flow njection analysis and reducing the time to control the quality of the process water.
Keywords: ion-elective electrode injection analysis; sample preparation; the uncertainty of the measurement systems; environmental monitoring